John Henry Newman-mistrz pióra dwóch wyznań? - Kuczok, Marcin (Studia Europaea Gnesnensia, 2016)
The article aims at answering the question whether John Henry Newman (1801-1890), a prolific writer of the Victorian era, can be considered a wordsmith whose writing reached the highest degree of artistic mastery. The paper analyzes the most important genres Newman employed in his Anglican and Catholic periods of life, and subsequently presents the opinions of literary critics regarding the quality and value of his writing. Finally, the author examines the impact of Newmans literary works on culture and art, as well as on literature of both his era and in the centuries to follow.